Clinical and molecular characterization of an almost complete ring chromosome 4 in two sisters, with recurrence due to gonadal mosaicism. Issue 4 (26th July 2021) - Phillips, Eliza A.; Caluseriu, Oana; Schlade-Bartusiak, Kamilla; Chernos, Judy; McLeod, D. Ross; Thomas, Mary Ann
Abstract : Autosomal ring chromosomes are rare cytogenetic findings that arise from breakage and fusion of the chromosome ends. Rings are mitotically unstable, usually sporadic and associated with a 'ring syndrome', characterized by a variable phenotype: growth retardation, no significant dysmorphisms and normal to moderately disabled intelligence. We describe the clinical features and molecular characterization of two sisters with ring chromosome 4. Karyotype analysis was performed on both sisters and parents. Chromosome microarray was performed on both sisters to delineate the breakpoint imbalance. Both sisters had a large ring 4 chromosome in the majority of cells analyzed on karyotype. Microarray results were identical in the sisters, showing a 55.8 kb duplication on the terminal 4p arm and a 1.5 Mb deletion on the terminal 4q arm. No genes of interest were identified in these regions. Parental karyotypes on lymphocytes and fibroblasts were normal, with no finding of mosaicism for the ring 4 chromosome. Polymorphic marker analysis revealed the maternal origin of the ring. To our knowledge, this is the first reported instance of a ring 4 chromosome recurring in siblings after extensive parental testing, which suggests this was due to maternal gonadal mosaicism.